Soil insects associated with sugarcane crop in Mato Grosso do Sul, Brazil - Crébio José Ávila; Gleiciele Caparróz; Viviane Santos; Ivana Fernandes da Silva (Ciência Rural, 2023)
ABSTRACT: Pest insects are one of the major factors affecting the productivity of sugarcane, and especially those associated with the soil, which damage the crop if not controlled. There is little information on the insect associated with the soil in the sugarcane crop in the state of Mato Grosso do Sul, Brazil. This study evaluated the occurrence, abundance and population variation of soil-associated insects in sugarcane crops in four counties in the state of Mato Grosso do Sul during a period from September 2009 to August 2010. For the capture of insects, deep in the soil trenches were (50 x 50 x 30 width x length x depth). It was observed that county of Maracaju has a high incidence of soil insects in sugarcane crop. Specimens of the family Scarabaeidae are abundant in sugarcane fields of the state of Mato Grosso do Sul, being Liogenys suturalis the predominant species. Soil insects of the Chrysomelidae family were found with greater abundance in Dourados and Naviraí while Noctuidae, represented only by the Hyponeuma taltula, occurred mainly in Dourados. Insects of the family Termitidae occur in sugarcane fields in the counties of Maracaju and Naviraí but not in Nova Alvorada do Sul and Dourados. Sphenophorus levis and Metamasius hemipterus were alsoreported in the sugarcane fields from Maracaju, being the occurrence these species the first record in the Mato Grosso do Sul State. The determined occurrence of different soil insects in the sugarcane fields may help in their management in the four counties studied.